Influências teóricas e políticas nas práticas educativas da rede ecovida de agroecologia - Nunes, Sidemar Presotto (2012)
The “Rede Ecovida de Agroecologia” is defined as part of "agroecological movement" Brazilian and Latin American. It was officially constituted in 1998 as an attempt to counteract some aspects of normative instruction of organic agriculture, but its origin goes back to the practical action of the Catholic Church through the “Teologia da Libertação”, from the 70s, the rapprochement with Marxism - in largely through said theology - and the emergence of an environmental movement that developed in some universities. Faced with the advance of modernization of brazilian agriculture, NGOs that later contributed to the establishment of Ecovida, put up, mostly as a consultant for social movements in relation to the development of technologies that were presented as alternatives the hegemonic process, besides contributing to the political organization of farmers through "popular education". The changes in the economic and political scenario, notably the globalization of capital and the fall of socialism, also promoted profound changes in the concepts and practice of educational policy and social movements, although in different ways. With the autonomy of social movements through the specialization of these due to more specific themes (syndicalism, the Landless Workers Movement, Movement of People Affected by Dams etc..), These NGOs also develop some degree of autonomy in relation to movements and continue to oppose the "development model of agriculture", while proposing the organization of ecological farmers and consumers through a new organizational form (farmer groups, ethics committees, centers etc.). That keeps the proposal for popular education developed in the previous period, but also incorporates the concepts that are being assumed by environmentalism in this new period. How do you propose that agroecology is also an educational process, the articulated projects of social change, one wonders, in order to understand its contradictions, which are the theoretical basis of this proposal and policies adopted by Ecovida and the agroecological movement. That is, what is the conception of man, society, nature, reality, educational practice, etc. Supported in field research and literature, we started with the study of seven of the twenty-seven centers currently existing Network, located in southern Brazil and insertion into the Joint National Agroecology Agroecology Movement and Latin America. From this work we can say that the educational practice of Ecovida corresponds to a kind of "eco popular education" that historically relied on the "Paulo Freire Method" of popular education and he spent associate a set of concepts and authors in the agroecology as the technical basis of production or of those who proposed its relationship with political practice. Changes in historical context altered the political subject of education Ecovida, which requires review the historical project.